PERANCANGAN BUKU POP-UP KESENIAN DONGKREK MADIUN MENGGUNAKAN TEKNIK PULL-TABS SEBAGAI UPAYA MENGENALKAN BUDAYA LOKAL KEPADA ANAK-ANAK - Hafizhuddin, Oni Nur; Riyanto, Darwin Yuwono; Hidayat, Wahyu (Jurnal Art Nouveau, 2017)
Dongkrek popularized in 1910 by Raden Bei Lo Prawirodipura who was a District Officer (post of village head level) in the area Caruban. Society at that time to hear the music of this form of musical art dongkrek 'dung' is derived from the drum or drums and the "crick" of a musical instrument called a match. From the sound of 'dung' on drums and "crick" in this match then came the name of art Dongkrek. According Walgito, that is currently staging Dongkrek art is rarely because there are two types of pertujukan Dongkrek. First, sakralkan ritual in which Dongkrek event logs in the village Mejayan starting with a procession of masks Dongkrek Dongkrek and delivery is only done in suro which is led by Mr. Dul Rokhim (chairman of the association Dongkrek Madison County). Second, the creation of a reception Dongkrek art, through dance performances Dongkrek inauguration. That needs attention at this time, when more and more rare these Dongkrek artists to perform because of the rarity pentasan no call for events in the environment, could be masyarakan especially children become less familiar with this Dongkrek art. Therefore, as an introduction to art Dongkrek Madiun, to be achieved in this research aims to design a pop-up book art using techniques Dongkrek Madiun pull-tabs as efforts to preserve local culture to children. Keywords: Design, pop-up books, Dongkrek, Mejayan village, Madiun